AXL is a potential therapeutic target in dedifferentiated and pleomorphic liposarcomas. Issue 1 (December 2015) - May, Caitlin; Garnett, Jeannine; Ma, XiaoYan; Landers, Sharon; Ingram, Davis; Demicco, Elizabeth; Al Sannaa, Ghadah; Vu, Tona; Han, Lixia; Zhang, Yi; Kivlin, Christine; Bolshakov, Svetlana; et al.
Abstract Background AXL is a well-characterized, protumorigenic receptor tyrosine kinase that is highly expressed and activated in numerous human carcinomas and sarcomas, including aggressive subtypes of liposarcoma. However, the role of AXL in the pathogenesis of well-differentiated (WDLPS), dedifferentiated (DDLPS), and pleomorphic liposarcoma (PLS) has not yet been determined. Methods Immunohistochemical analysis of AXL expression was conducted on two tissue microarrays containing patient WDLPS, DDLPS, and PLS samples. A panel of DDLPS and PLS cell lines were interrogated via western blot for AXL expression and activity and by ELISA for growth arrest-specific 6 (GAS6) production. AXL knockdown was achieved by siRNA or shRNA. The effects of AXL knockdown on cell proliferation, migration, and invasion were measured in vitro. In addition, AXL shRNA-containing DDLPS cells were assessed for their tumor-forming capacity in vivo. Results In this study, we determined that AXL is expressed in a subset of WDLPS, DDLPS, and PLS patient tumor samples. In addition, AXL and its ligand GAS6 are expressed in a panel of DDLPS and PLS cell lines. We show that the in vitro activation of AXL via stimulation with exogenous GAS6 resulted in a significant increase in cell proliferation, migration, and invasion in DDLPS and PLS cell lines. Transient knockdown of AXL resulted in attenuation of these protumorigenic phenotypes in vitro. Stable AXL knockdown not only decreased migratory and invasive characteristics of DDLPS and PLS cells in vitro but also significantly diminished tumorigenicity of two dedifferentiated liposarcoma xenograft models in vivo. Conclusions Our results suggest that AXL signaling contributes to the aggressiveness of DDLPS and PLS, and that AXL is therefore a potential therapeutic target for treatment of these rare, yet devastating tumors.